Dissecting the Genetic Architecture of Cystatin C in Diversity Outbred Mice. Issue 7 (1st July 2020) - Huda, M Nazmul; VerHague, Melissa; Albright, Jody; Smallwood, Tangi; Bell, Timothy A; Que, Excel; Miller, Darla R; Roshanravan, Baback; Allayee, Hooman; Manuel de Villena, Fernando Pardo; Bennett, Brian J
Abstract: Plasma concentration of Cystatin C (CysC) level is a biomarker of glomerular filtration rate in the kidney. We use a Systems Genetics approach to investigate the genetic determinants of plasma CysC concentration. To do so we perform Quantitative Trait Loci (QTL) and expression QTL (eQTL) analysis of 120 Diversity Outbred (DO) female mice, 56 weeks of age. We performed network analysis of kidney gene expression to determine if the gene modules with common functions are associated with kidney biomarkers of chronic kidney diseases. Our data demonstrates that plasma concentrations and kidney mRNA levels of CysC are associated with genetic variation and are transcriptionally coregulated by immune genes. Specifically, Type-I interferon signaling genes are coexpressed with Cst3 mRNA levels and associated with CysC concentrations in plasma. Our findings demonstrate the complex control of CysC by genetic polymorphisms and inflammatory pathways.